The global structure of marine cleaning mutualistic networks - Juan Pablo Quimbayo; Mauricio Cantor; Murilo S. Dias; Alexandra S. Grutter; Simon Gingins; Justine H. A. Becker; Sergio R. Floeter (Global Ecology and Biogeography, 2018)
Aim We studied the underlying biotic and abiotic drivers of network patterns in marine cleaning mutualisms (species feeding upon ectoparasites and injured tissues of others) at large spatial scales. Location Eleven marine biogeographical provinces. Time period 1971–2018. Major taxa studied Reef fish and shrimps. Methods We combined field and literature data to test whether recurrent patterns in mutualistic networks (nestedness, modularity) describe the distributions of marine cleaning interactions. Nested network structures suggest that some cleaner species interact with many clients while the others clean fewer, predictable subsets of these clients; modular network structures suggest that cleaners and clients interact within defined, densely connected subsets of species. We used linear mixed models to evaluate whether the life‐history traits of cleaners contribute to the emergence of these patterns locally and whether environmental and geographical factors influence the network structures. Results Marine cleaning networks were more nested than modular. Nestedness was prevalent in communities with dedicated cleaners (ones that feed exclusively by cleaning), whereas communities with only facultative cleaners (ones that clean opportunistically) were generally unstructured. Cleaner type and taxa were the only traits shaping networks, with dedicated fish cleaners contributing disproportionally more than facultative cleaners and shrimps to the emergence of nestedness. Although cleaner species seem concentrated around the tropics and biodiversity centres, we did not detect an influence of environmental and geographical factors on network structures. Main conclusions Dedicated species are key in shaping the structure of marine cleaning mutualistic networks. By relying exclusively on cleaning to feed, dedicated cleaners interact with most of the available clients and form the network core, whereas the opportunistic facultative species tend to clean the most common clients. We hypothesize that trophic niche variation and phenotypic specialization are major drivers of this asymmetry in marine mutualisms. Our study strengthens the links between biotic interactions at the community level and the distribution of species and specializations at larger spatial scales.